2006
DOI: 10.1016/j.ejphar.2006.03.057
|View full text |Cite
|
Sign up to set email alerts
|

Vascular endothelin ETB receptor-mediated contraction requires phosphorylation of ERK1/2 proteins

Abstract: In cardiovascular diseases, endothelin type B (ET B ) receptors in arterial smooth muscle cells are upregulated. The present study revealed that organ culture of rat mesenteric artery segments enhanced endothelin ET B receptor-mediated contraction paralleled with increase in the receptor mRNA and protein expressions. The endothelin ET B receptor-mediated contraction was associated with increase in phosphorylation of extracellular regulation kinase 1 and 2 (ERK1/2) proteins and elevated levels of intracellular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
17
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 32 publications
1
17
0
Order By: Relevance
“…The Raf-1/MEK/ERK signal transduction cascade has traditionally only been associated with growth-related processes such as activation of gene transcription [11] . However, recent studies have shown that this pathway can be involved in other, seemingly unrelated processes, such as vasoconstriction [6][7][8] . As contractile agonists have been shown to stimulate Raf-1 kinase in vascular smooth muscle cells grown in culture [18,32,33] , it is possible that a similar activation in blood vessels mediates vasoconstriction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Raf-1/MEK/ERK signal transduction cascade has traditionally only been associated with growth-related processes such as activation of gene transcription [11] . However, recent studies have shown that this pathway can be involved in other, seemingly unrelated processes, such as vasoconstriction [6][7][8] . As contractile agonists have been shown to stimulate Raf-1 kinase in vascular smooth muscle cells grown in culture [18,32,33] , it is possible that a similar activation in blood vessels mediates vasoconstriction.…”
Section: Discussionmentioning
confidence: 99%
“…There is convincing evidence to explain that the downstream effectors, MEK/ERK, regulate vascular contraction [6][7][8] . However, modulation of smooth muscle contraction by MEK/ERK has been shown to be directly regulated by PKC rather than its classical activator, Raf-1 [7,9,10] .…”
mentioning
confidence: 99%
“…It was previously shown that sensitivity to NA increased after a 7-day serum-free organ culture of rabbit mesenteric arteries [22]. Similarly, it was reported that sensitivity to an ET B agonist, sarafotoxin 6c increased after a 1-day serum-free organ culture of rat mesenteric arteries [7,11,18,19]. Several explanations are available to the increased sensitivity to agonists after serumfree organ culture; 1) up-regulation of receptor to each agonist, 2) activation of intercellular signaling pathways such as tyrosine kinase or protein kinase C (PKC), 3) increase in resting membrane potential by decreasing the expression and/or function of K + channels, or by increasing the expression and/or function of voltage-dependent Ca 2+ channels and transient receptor potential channel (TRPC), 4) production of reactive-oxygen species (ROS).…”
Section: Discussionmentioning
confidence: 98%
“…Several explanations are available to the increased sensitivity to agonists after serumfree organ culture; 1) up-regulation of receptor to each agonist, 2) activation of intercellular signaling pathways such as tyrosine kinase or protein kinase C (PKC), 3) increase in resting membrane potential by decreasing the expression and/or function of K + channels, or by increasing the expression and/or function of voltage-dependent Ca 2+ channels and transient receptor potential channel (TRPC), 4) production of reactive-oxygen species (ROS). In rat mesenteric arteries cultured for 1 day in the serum-free medium, the upregulation of alpha 1A adrenoreceptor [3] and ET B receptor [7,11,18,19] was reported. With regard to the activation of intercellular signal pathways, a non-receptor tyrosine kinase, src-dependent increase of NA-induced contraction was reported in rat mesenteric arteries cultured in the serumfree condition for 2-3 days [16].…”
Section: Discussionmentioning
confidence: 99%
“…These results failed to demonstrate that there is alteration of contractile proteins in our system. Moreover, in previous investigations, organ culture of rat mesenteric arteries has been revealed to up-regulate vascular receptors like ET B receptors [27, 51]. The enhanced expression of the ET B receptors occurs through de novo transcription and is again not the result of an increase in general vascular reactivity [28].…”
Section: Discussionmentioning
confidence: 99%